The antiapoptotic gene survivin is highly expressed in human chondrosarcoma and promotes drug resistance in chondrosarcoma cells in vitro - Lechler, Philipp (BioMed Central, 2011)
BACKGROUND: Chondrosarcoma is virtually resistant to chemotherapy and radiation therapy. Survivin, the smallest member of the inhibitor of apoptosis protein family, is a critical factor for tumor progression and resistance to conventional therapeutic approaches in a wide range of malignancies. However, the role of survivin in chondrosarcoma has not been well studied. We examined the importance of survivin gene expression in chondrosarcoma and analysed its influences on proliferation, apoptosis and resistance to chemotherapy in vitro. METHODS: Resected chondrosarcoma specimens from which paraffin-embedded tissues could be extracted were available from 12 patients. In vitro experiments were performed in human chondrosarcoma cell lines SW1353 and Hs819.T. Immunohistochemistry, immunoblot, quantitative PCR, RNA interference, gene-overexpression and analyses of cell proliferation and apoptosis were performed. RESULTS: Expression of survivin protein was detected in all chondrosarcoma specimens analyzed, while undetectable in adult human cartilage. RNA interference targeting survivin resulted in a G(2)/M-arrest of the cell cycle and led to increased rates of apoptosis in chondrosarcoma cells in vitro. Overexpression of survivin resulted in pronounced resistance to doxorubicin treatment. CONCLUSIONS: These findings indicate that survivin plays a role in the pathogenesis and pronounced chemoresistance of high grade chondrosarcoma. Survivin antagonizing therapeutic strategies may lead to new treatment options in unresectable and metastasized chondrosarcoma.